2018
DOI: 10.3847/1538-4357/aaa6ca
|View full text |Cite
|
Sign up to set email alerts
|

M101: Spectral Observations of H ii Regions and Their Physical Properties

Abstract: By using the Hectospec 6.5 m Multiple Mirror Telescope (MMT) and the 2.16 m telescope of National Astronomical Observatories, Chinese Academy of Sciences (NAOC), we obtained 188 high signal-to-noise ratio (S/N) spectra of H ii regions in the nearby galaxy M101, which are the largest spectroscopic sample of H ii regions for this galaxy so far. These spectra cover a wide range of regions on M101, which enables us to analyze two dimensional distributions of its physical properties. The physical parameters are der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 101 publications
(142 reference statements)
4
18
0
Order By: Relevance
“…For presentation purposes, the slit length is set to 7 arcsec; however, a 0.7 arcsec × 110.7 arcsec slit was used for (a) and a 0.7 arcsec × 118.7 arcsec slit was used for (b). Hu et al 2018). We conclude that this source is most likely an RSG with an effective temperature in the 3000-4000 K range, matching the classification based on mid-IR photometry presented in Lau et al (2019).…”
Section: Cxou J1403143+541807: An Rsg In Ngc 5457supporting
confidence: 80%
See 1 more Smart Citation
“…For presentation purposes, the slit length is set to 7 arcsec; however, a 0.7 arcsec × 110.7 arcsec slit was used for (a) and a 0.7 arcsec × 118.7 arcsec slit was used for (b). Hu et al 2018). We conclude that this source is most likely an RSG with an effective temperature in the 3000-4000 K range, matching the classification based on mid-IR photometry presented in Lau et al (2019).…”
Section: Cxou J1403143+541807: An Rsg In Ngc 5457supporting
confidence: 80%
“…5b). After fitting Gaussian profiles to these lines, we calculated the radial velocity of the source to be 295 ± 16 km s −1 , consistent with the radial velocity of NGC 5457 at the position of the ULX (Hu et al 2018).…”
Section: [Lb2005] Ngc 5457 X26: a Nebulasupporting
confidence: 61%
“…First, the degeneracy between q PAH and f abs can be disentangled if either q PAH is determined using MIR spectra observed via MIRI or f abs is derived from MIR photometry based on the empirical estimation of the total IR luminosity (e.g., Boquien et al 2010;Elbaz et al 2010;Lin et al 2016). Furthermore, a combination of these high spatial resolution observations with spectra of H II regions (e.g., Berg et al 2015;Croxall et al 2016;Lin et al 2017;Hu et al 2018) or integral field spectroscopy observations (Sánchez et al 2012) in nearby galaxies will enable us to investigate whether and how the PAH-age relation depends on the local environment at the star cluster scale.…”
Section: Discussionmentioning
confidence: 99%
“…The Oxygen abundance profile of NGC 5457 shown here, does not show any clear flattening out to 1.2R 25 . However, Hu et al (2018) have found that a flattening is shown at ∼0.8R 25 (consistent with blue curve) when adopting the metallicity indicator from Kobulnicky & Kewley (2004). This serves as a reminder that different methods of measuring Oxygen abundance may play a significant role in determining the detailed features of the profile.…”
Section: The Radial Inflow Rate and Metallicity In Thementioning
confidence: 64%